2007
DOI: 10.1111/j.1472-8206.2007.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of anxiety in mice

Abstract: Among the multiple possibilities to study human pathologies, animal models remain one of the most used pathways. They allow to access to unavailable answers in human patients and to learn about mechanisms of action of drugs. Primarily developed with rats, animal models in anxiety have been adapted with a mixed success for mice, an easy-to-use mammal with better genetic possibilities than rats. In this review, we have focused on the most used animal models in anxiety in mice. Both conditioned and unconditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
2
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(194 citation statements)
references
References 32 publications
12
158
2
14
Order By: Relevance
“…Even if one considers that current animal models aim to reflect several factors (such as low cost, speed, and reproducibility) in addition to the dominant theoretical views related to the pathogenesis of specific disorders and the accepted action mechanism of psychotropic drugs, they have produced a significant contribution to the discovery of new drugs and the understanding of the neurobiology of psychiatric diseases. 8 Despite the theoretical idea that a model should reproduce all features of the phenomenon under investigation, this is rarely (if ever) achieved, reflecting the complex manifestations of psychiatric disorders and the huge cognitive differences between humans and laboratory animals (mainly rodents, e.g., rats, mice, hamsters, gerbils, guinea pigs). Animal models of anxiety, therefore, do not intend to replicate all features and symptoms of a specific anxiety disorder but rather generate a state of anxiety that could be related to these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Even if one considers that current animal models aim to reflect several factors (such as low cost, speed, and reproducibility) in addition to the dominant theoretical views related to the pathogenesis of specific disorders and the accepted action mechanism of psychotropic drugs, they have produced a significant contribution to the discovery of new drugs and the understanding of the neurobiology of psychiatric diseases. 8 Despite the theoretical idea that a model should reproduce all features of the phenomenon under investigation, this is rarely (if ever) achieved, reflecting the complex manifestations of psychiatric disorders and the huge cognitive differences between humans and laboratory animals (mainly rodents, e.g., rats, mice, hamsters, gerbils, guinea pigs). Animal models of anxiety, therefore, do not intend to replicate all features and symptoms of a specific anxiety disorder but rather generate a state of anxiety that could be related to these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that tannic acid has been shown to possess a non-selective inhibitory effect on MAO, causing a general elevation of monoaminergic neurotransmission in the brain [45]. Other polyphenolic compounds such as rosmarinic acid and its metabolite have also been reported to have antidepressant activity.…”
Section: Discussionmentioning
confidence: 99%
“…animal filters out extraneous information and protects against sensory 234 overload for (review see (Swerdlow et al, 2008) Swerdlow et al, 2008). In rodents the startle response itself is commonly 240 used to assess emotional reactivity and the effects of anti-anxiety drugs 241 (Bourin et al, 2007;Grillon, 2008;McCaughran et al, 2000). Species and 242 strains within species differ in their regulation of startle and PPI 243 (Swerdlow et al, 2008).…”
Section: Growth and Organ Weights 176mentioning
confidence: 99%